Policies and practice of solid organ donation amongst people living with HIV in Canada: time for education and re-evaluation - Branka Vulesevic; Darren Lauscher; Deepali Kumar; Ruth Sapir-Pichhadze; Jean Tchervenkov; Jonathan B. Angel; Cameron Wolfe; Cecilia T. Costiniuk (HIV Research & Clinical Practice)
The numbers of organ donors in Canada and the USA fall short of increasing demand, resulting in increased morbidity, poor health outcomes, higher medical costs and death of many individuals waitlisted for transplantation. In the US, since 2013 when the US HIV Organ Policy Equity (HOPE) Act lifted the ban on organ donation between people living with HIV, the option of using organs from People with HIV became a reality. In Canada, HIV diagnosis was an exclusion criterion to organ donation until 2017, when permission was granted if requirements for ‘exceptional distribution’ could be met. Still, donation of organs from people with HIV poses challenges. Herein, we overview policies involving donors with HIV in Canada in order to inform healthcare providers, researchers and the community. We also advocate for the need to reassess these policies, highlight educational needs and engage interest in advancing research to inform policy reforms.